THE EFFECTIVENESS OF THE APPLICATION OF BLENDED LEARNING TO SUPPORT THE PROFESSIONALISM OF MATHEMATICS LECTURERS: EFEKTIVITAS PENERAPAN BLENDED LEARNING UNTUK MENDUKUNG PROFESIONALISME DOSEN MATEMATIKA - Dwi Risky Arifanti; Alauddin; Hengki (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
Investigations about the effectiveness of the application of blended learning today have been widely studied from the perspective of students. However, there is still little literature and findings on the effectiveness of blended learning in improving the professionalism of lecturers, especially in the field of mathematics. Furthermore, to support the implementation of blended learning, we use the Google Classroom application. Therefore, this study aims to investigate and describe the effectiveness of the application of blended learning to improve the professionalism of mathematics lecturers which includes dimensions of knowledge, beliefs, and attitudes. We used an Action Research design with one group post-test, where data were taken with several classes and the same treatment to achieve the research objectives. We involved two lecturers in the mathematics education study program with 34 students enrolled in the lecture. Furthermore, the research procedure includes three stages, namely preparation, implementation, and filling out data collection instruments. We used descriptive statistical analysis to obtain research objectives in the form of obtaining average scores, maximum values, minimum values, and standard deviations. Finally, the analysis results show: (1) the lecturer's knowledge is in the high category, (2) the lecturer's confidence is in the active category for each meeting, and (3) the expected attitude of lecturers in blended learning is in the positive category, so it can be concluded that the application of blended-learning is effective in improving the professionalism of mathematics lecturers.